Study And Analysis Of An Islamic Finance Window In Algeria - Requirements For Separation Of Conventional And Islamic Bank Activities At The Housing Bank Level - Azzaoui, Khaled; Bedrouni, Aissa (جامعة الوادي - University of Eloued, 2020)
The objective of our study is to analyze the levels of separation between the Islamic window and its classic bank during the activity. Through an empirical study within the window of the Housing Bank, we will provide elements of answers to our problem. The purpose of this article is to look at the practical details of Islamic activity in windows, while emphasizing the levels of separation between the traditional bank and its Islamic window. First, we carry out a diagnosis of the Islamic banking system in Algeria which is made up of two Islamic banks and conventional banks with Islamic products. In the following, we will present the Housing Bank and the establishment of its Islamic window, while emphasizing the accounting separation of the window, the separation of the information system and the work of the Shari committee.
مقال
Keywords: Islamic window; Islamic products; conventional banks; Sharia standards.